Characteristics of an exploited tropical shallow - water demersal fish community in Malaysia - Chan, E. H.; Liew, H. C. (1986)
Trawling provided insights into the characteristics of an exploited tropical shallow-water demersal fish community. A total of 6,565 fish specimens weighing 285 kg were caught at 20 sampling stations. In all,139 species belonging to 50 families were recorded. The major families ranked by weight were Dasyatidae (19.7%), Synodontidae (18.3%), Paralichthyidae (8.9%), Dactylopteridae (8%), Nemipteridae (5.3%), Lagocephalidae (5.2%), Priacanthidae (5%); and Mullidae (4%). The overall fish trawled consisted of 53% food fish and 47% trash fish. The demersal fish community could be partitioned into four trophic groups, i.e., large zoobenthos feeders, intermediate predators, small demersal zoobenthos feeders and small demersal zooplankton feeders. Small crustaceans played an important role as food resources for all the trophic groups. They were the major food for small demersal zoobenthos feeders, the dominant group, and large zoobenthos feeders. Analysis of growth characteristics of ten common species using length-frequency data showed that Saurlda elongata and Trachlnocephalus myops ·(Synodontidae) and Dactyloptena orlentalis (Daetylopteridae) had higher growth rates than the other fishes in the community. Exploitation rates of these three species by trawlers were also high although they have little commercial value. Annual recruitment patterns. for the demersal fishes were generally protracted showing a single pulse, although some species have a second minor pulse.